Optimized, automated and cGMP-compliant synthesis of the HER2 targeting [68Ga]Ga-ABY-025 tracer - Emma Jussing; Mélodie Ferrat; Mohammad M. Moein; Henrik Alfredéen; Tetyana Tegnebratt; Klas Bratteby; Erik Samén; Joachim Feldwisch; Renske Altena; Rimma Axelsson; Thuy A. Tran (SpringerOpen, 2023)
Abstract Background The Affibody molecule, ABY-025, has demonstrated utility to detect human epidermal growth factor receptor 2 (HER2) in vivo, either radiolabelled with indium-111 (111In) or gallium-68 (68Ga). Using the latter, 68Ga, is preferred due to its use in positron emission tomography with superior resolution and quantifying capabilities in the clinical setting compared to 111In. For an ongoing phase II study (NCT05619016) evaluating ABY-025 for detecting HER2-low lesions and selection of patients for HER2-targeted treatment, the aim was to optimize an automated and cGMP-compliant radiosynthesis of [68Ga]Ga-ABY-025. [68Ga]Ga-ABY-025 was produced on a synthesis module, Modular-Lab PharmTracer (Eckert & Ziegler), commonly used for 68Ga-labelings. The radiotracer has previously been radiolabeled on this module, but to streamline the production, the method was optimized. Steps requiring manual interactions to the radiolabeling procedure were minimized including a convenient and automated pre-concentration of the 68Ga-eluate and a simplified automated final formulation procedure. Every part of the radiopharmaceutical production was carefully developed to gain robustness and to avoid any operator bound variations to the manufacturing. The optimized production method was successfully applied for 68Ga-labeling of another radiotracer, verifying its versatility as a universal and robust method for radiosynthesis of Affibody-based peptides. Results A simplified and optimized automated cGMP-compliant radiosynthesis method of [68Ga]Ga-ABY-025 was developed. With a decay corrected radiochemical yield of 44 ± 2%, a radiochemical purity (RCP) of 98 ± 1%, and with an RCP stability of 98 ± 1% at 2 h after production, the method was found highly reproducible. The production method also showed comparable results when implemented for radiolabeling another similar peptide. Conclusion The improvements made for the radiosynthesis of [68Ga]Ga-ABY-025, including introducing a pre-concentration of the 68Ga-eluate, aimed to utilize the full potential of the 68Ge/68Ga generator radioactivity output, thereby reducing radioactivity wastage. Furthermore, reducing the number of manually performed preparative steps prior to the radiosynthesis, not only minimized the risk of potential human/operator errors but also enhanced the process' robustness. The successful application of this optimized radiosynthesis method to another similar peptide underscores its versatility, suggesting that our method can be adopted for 68Ga-labeling radiotracers based on Affibody molecules in general. Trial registration: NCT, NCT05619016, Registered 7 November 2022, https://clinicaltrials.gov/study/NCT05619016?term=HER2&cond=ABY025&rank=1